A constituição da identidade docente em Educação Física na Base Nacional Comum Curricular: limites e possibilidades à luz da pedagogia freireana - Vieira, Luiz Renato Assunção (2020)
The aim of this study is to analyze the BNCC in Physical Education for the elementary school from the perspective of the pedagogy proposed by Paulo Freire, explaining in which curricular perspective this document contributes to the constitution of the teacher/ professional identity in Physical Education and, based on this analysis, to investigate what are the possibilities for a critical-Freirean curriculum in Physical Education that constitutes a teacher identity as a critical-liberating educator. This investigation is relevant because the teacher identity in Physical Education is confused with other professional identities according to the different curricular proposals. This qualitative research uses bibliographic research and documentary analysis to understand how the history of Physical Education in Brazilian schools and the different curricular theories constitute different teachers identities. For this we are based on some theoretical bases that allow us to establish parameters to analyze the constitution of the teacher identity in Physical Education in BNCC, some of the main ones are: Antonio Flavio Barbosa Moreira, Thomaz Tadeu da Silva, Selma Garrido Pimenta, Paulo Ghiraldelli Júnior, Valter Bracht, Mário Luiz Ferrari Nunes and Marcos Garcia Neira. Concomitantly, we are based on Paulo Freire's Liberating education, establishing the Freirean categories of dialogue and praxis as analytical categories for thinking about the limits of the curriculum proposal contained in the BNCC. The results of this research show that BNCC presents several aspects of a traditional curriculum proposal that give Physical Education characteristics of the “banking education” denounced by Paulo Freire and constitute an alienated and alienating teacher identity. It is from these results that we think about the possibilities of a critical Physical Education curriculum based on Freire's Liberating education understood from the dialogue and that, based on curricular praxis, contribute to the constitution of a teacher identity in Physical Education as a critical-liberating educator.